(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
In this article, the advantages of folklore examples in the formation and development of the feeling of national pride in students are revealed. Also, attention is paid to the advice of parents, grandfathers and grandmothers in educating the young generation through stories and fairy tales, and forming a sense of national pride in them.